KOMIK SEBAGAI MEDIA PEMBELAJARAN MATERI LARUTAN ASAM DAN BASA DI KELAS XI SMK NEGERI 7 PONTIANAK - Siti Vera (Jurnal Ilmiah Ar-Razi, 2018)
This research was motivated by the low learning outcomes of students in chemistry subjects, especially the material of acid and base solutions. The purpose of this study was to determine the use of comics as a learning medium for acid and alkaline solution material as well as student learning outcomes before and after using comics as a learning medium in class XI SMK Negeri 7 Pontianak. The method in this study is an experiment with the form of pre-experimental research. Data collectors used measurement techniques and data collection tools namely pretest-posttest questions. Data analysis used statistical analysis techniques. Based on the results of the study it was found that there were significant differences in student learning outcomes between before and after using comics as a learning medium for material of acid and base solutions in class XI SMK Negeri 7 Pontianak. This difference is obtained from the comparison of the average pretest and posttest results of students is 25,793 and 82,379. This means that the posttest results are greater than the results of the pretest. Based on statistical analysis with ttest, it is known that the results of the comparison of the results of the pretest is greater than the ttable, which is 16.090 > 2.048 which indicates that Ho rejected and Ha accepted. The comparison value of tcount the posttest result is greater than ttable that is 59.668 > 2.048 indicates that Ho is rejected and Ha is accepted. If Ho is rejected Ha accepted means there is a significant difference between the results of the posttest and the results of the students' pretest. So it can be concluded that comics can be used as a learning medium in improving the learning outcomes of chemistry in material of acid and base solutions in class XI SMK Negeri 7 Pontianak.